Ictal but Not Interictal Epileptic Discharges Activate Astrocyte Endfeet and Elicit Cerebral Arteriole Responses - Gomez-Gonzalo, Marta; Losi, Gabriele; Brondi, Marco; Uva, Laura; Sulis-Sato, Sebastian; De Curtis, Marco; Ratto, Gian Michele; Carmignoto, Giorgio (Frontiers in Cellular Neuroscience, 2011)
Activation of astrocytes by neuronal signals plays a central role in the control of neuronal activity-dependent blood flow changes in the normal brain. The cellular pathways that mediate neurovascular coupling in the epileptic brain remain, however, poorly defined. In a cortical slice model of epilepsy, we found that the ictal, seizure-like discharge, and only to a minor extent the interictal discharge, evokes both a Ca2+ increase in astrocyte endfeet and a vasomotor response. We also observed that rapid ictal discharge-induced arteriole responses were regularly preceded by Ca2+ elevations in endfeet and were abolished by pharmacological inhibition of Ca2+ signals in these astrocyte processes. Under these latter conditions, arterioles exhibited after the ictal discharge only slowly developing vasodilations. The poor efficacy of interictal discharges, compared with ictal discharges, to activate endfeet was confirmed also in the intact in vitro isolated guinea pig brain. Although the possibility of a direct contribution of neurons, in particular in the late response of cerebral blood vessels to epileptic discharges, should be taken into account, our study supports the view that astrocytes are central for neurovascular coupling also in the epileptic brain. The massive endfeet Ca2+ elevations evoked by ictal discharges and the poor response to interictal events represent new information potentially relevant to interpret data from diagnostic brain imaging techniques, such as functional magnetic resonance, utilized in the clinic to localize neural activity and to optimize neurosurgery of untreatable epilepsies.